Fueling young athletes - Mangieri, Heather R. 1974- (Champaign, IL Human Kinetics, 2017)
"Fueling Young Athletes stresses the importance of balanced daily nutrition as part of an overall eating plan for health, growth, development, and sport performance and shows how to implement that plan"--Publisher's description.
Part 1. Sport nutrition for today's athletes: Building a champion ; Day-to-day nutrition for healthy growth -- Part 2. Nutrition needs for sports and individual goals: Fueling and hydrating for sport ; Adjusting body composition to reach your goals ; Fueling for game day ; Understanding supplements ; Identifying and dealing with disordered eating -- Part 3. Customize your sport nutrition plan: Creating your personal plan ; Breaking down barriers to healthy eating -- Part 4. Recipes: Liquid-fuel recipes ; Solid-fuel recipes -- About the author.
Includes bibliographical references (pages 209-219) and index.
Keywords: Nutrition -- Popular works; Athletes -- Nutrition -- Popular works; Exercise -- Physiological aspects -- Popular works